(3TQM MeGSI CHj JeGes - (3CHi GdMLGL jhSa Hf SdjeGf Hf YjSis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3TGWHg (B((3GdCfOdS(B) s)
(3ChdgG (B:s
(3HGH GdCOH (B( (3gh GdHGH GdKGdK HJbSjeg (B) (3bGajg GdCda bGd bjS Hf GdNWje GdCfUGQi(B: (3heG HYV GdEbGeI ai OjGQ jgGf HgG GdaJi EdG YfGA s
(3BNQgG (B:s
(3hGfJgGA JCdjag hJOejfg hJUfjag jhe GdNejS ddfUa Pi GdbYOg ef GdSfI GdeDQNI hCSCd Gddg ef GdfhGad aVdg s
(3fSNI KGfjIs
(3gPG GdLRA ef GdfSNI GdChdi faSgG GdLRA GdChd GdCMeOjg (B-(3JhfS (B4536s
(3HChdgG hbajI Ydi LGeY GdRjJhfg HJhfS HJGQjN (B1256s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs